Genomic Changes in an Attenuated ZB Strain of Foot-and-Mouth Disease Virus Serotype Asia1 and Comparison with Its Virulent Parental Strain - Aiguo Xin; Mingwang Zhu; Zhenqi Peng; Qi Hu; Chenhong Shi; Defang Liao; Jihua Wang; Huachun Li (International Journal of Genomics)
The molecular basis of attenuation of foot-and-mouth disease virus (FMDV) serotype Asia1 ZB strain remains unknown. To understand the genetic changes of attenuation, we compared the entire genomes of three different rabbit-passaged attenuated ZB strains (ZB/CHA/58(att), ZBRF168, and ZBRF188) and their virulent parental strains (ZBCF22 and YNBS/58). The results showed that attenuation may be brought about by 28 common amino acid substitutions in the coding region, with one nucleotide point mutation in the 5′-untranslated region (5′-UTR) and another one in the 3′-UTR. In addition, a total of 21 nucleotides silent mutations had been found after attenuation. These substitutions, alone or in combination, may be responsible for the attenuated phenotype of the ZB strain in cattle. This will contribute to elucidation of attenuating molecular basis of the FMDV ZB strain.